Kajian Pustaka: Pentingnya Menerapkan Prinsip Pendidikan Adab Sejak Dini Untuk Pembentukan Pribadi Yang Berkarakter - Briliana Firdaus; Elan Sumarna; Ganjar Eka Subakti (Faculty Ushuluddin, Adab, and Dakwah Institut Agama Islam Negeri (IAIN) Palangka Raya, 2026)
Adab education from early childhood plays a crucial role in shaping children’s character. In practice, however, it is often narrowly understood as politeness, compliance, and obedience to rules. This study aims to analyze the concepts, pedagogical mechanisms, core values, and implementation strategies of adab education within family, school, community, and digital environments. The study employed an integrative literature review by selecting relevant literature on adab education, character education, early childhood, family-based parenting, role modelling, habituation, emotional regulation, and digital education. The data were analyzed through thematic coding, conceptual comparison, and critical synthesis. The findings indicate that adab constitutes a value orientation that integrates moral knowledge, spiritual awareness, self-regulation, responsibility, empathy, and social action. Adab education cannot be effectively implemented solely through verbal advice or the enforcement of rules. Instead, it requires consistent adult role modelling, meaningful habituation, reflective dialogue, prosocial experiences, logical consequences, and collaboration between families and schools. This review proposes a five-stage implementation model comprising value consensus, role modelling, routines, dialogue and reflection, and authentic assessment. Therefore, the effectiveness of adab education is determined more by the consistency of the educational ecology and the quality of interactions than by the number of rules imposed on children.